Give Growth and Macroeconomic Stability in Russia a Chance : Harden Budgets by Eliminating Nonpayments - Pinto, Brian (World Bank, Washington, DC, 2015)
The authors analyze the links between Russias disappointing growth performance in the second half of the 1990s, its costly and unsuccessful stabilization, the macroeconomic meltdown of 1998, and the spectacular rise of non-payments. Non-payments flourished in an environment of fundamental inconsistency between a macroeconomic policy geared at sharp disinflation, and a microeconomic policy of bailing enterprises out through soft budget constraints. Heavy untargeted implicit subsidies flowing through the non-payments system (amounting to 10 percent of GDP annually) have stifled growth, contributed to the August 1998 meltdown, through their impact on public debt, and have made at best a questionable contribution to equity. Dismantling this system must be a top priority, along with promoting enterprise restructuring and growth (by hardening budget constraints) and medium-term macroeconomic stability (by reducing the size of subsidies). Getting the government out of the non-payments system means settling all appropriately controlled budgetary expenditures on time, and in cash, and eschewing spending arrears, thereby setting an example for enterprises, and laying the groundwork for eliminating tax offsets at all levels of government, and insisting on cash tax payments. To stop energy-related subsidies, would require not only that the government pay its own energy bills on time, and in cash, but also that the energy monopolies be empowered to disconnect non-paying clients. This will enable the government to insist that the energy monopolies in turn pay their own taxes in full, and on time.